Peran Tokoh Agama terhadap Komunikasi Keluarga dalam Pengambilan Keputusan Pernikahan Dini di Madura - Janah, Defi Asiatul; Pramudita, Yusvi Nur; Kurniasari, Netty Dyah (CV. ITTC INDONESIA, 2024)
Early marriage in Indonesia, especially in areas with strong traditions, for example in Madura, is a complex and urgent social problem. According to the latest data from UNICEF, Indonesia is ranked fourth in the world in terms of early marriage cases. Family communication between parents and children is an important aspect in decision-making related to early marriage. Madurese society, known for its strong cultural and religious values, often relies on advice and guidance from religious figures in various aspects of life including marriage. This study aims to explore the role of religious figures in family communication related to early marriage decision-making in Madura. The study used a qualitative approach with a phenomenological design, which allows researchers to understand the experiences and views of informants in depth. The results of this study indicate that Madurese society respects religious figures, especially kiai as role models. The role of religious figures as social spiritual legitimacy, family communication mediators and emotional motivational support is very significant in family communication in early marriage decision-making in Madura.